Analysis of design goals of cryptography algorithms based on different components - Ali Mohammad Norouzzadeh Gil Molk; Mohammad Reza Aref; Reza Ramazani Khorshiddoust (Institute of Advanced Engineering and Science, 2021)
Cryptography algorithms are a fundamental part of a cryptographic system that is designed and implemented to increase information security. They are the center of attention of experts in the information technology domains. Although the cryptography algorithms are implemented to attainthe goals such as confidentially, integrity and authenticity of designing, but other matters that must be noticed by designers include speed, resource consumption, reliability, flexibility, usage type and so on. For the useful allocation of hardware, software, human resources, etc., it is important to identify the role of each of the factors influencing the design of cryptographic algorithms to invest in the development of cryptographic knowledge.This paper examines 1700 papers, documents and technical reports of international journals in the specific lengthy period (1978-2019), and the goal of the design and implementation of cryptography algorithms in a different period is extracted. Using a statistical population that consists of time and the number of documents in a long time and also avariety of data, leads this study to have a reliable result and attract the attention of designers.The results show that in recent years, attention tonew usage such as IoT and telemedicine, as well as lightweight cryptography, has increased to achieve the main goals.